Implementation Of Bloom’s Taxonomy In Understanding Taxation Documents Towards Learning Outcomes: Learning Motivation As Moderation - Reni Hariyani; Fenti Sofiani (Kusuma Negara Business School, 2021)
This study aims to determine significantly the implementation of Bloom's Taxonomy and understanding of tax documents that affect the learning outcomes of Tax Administration with learning motivation as a moderating variable. Research methods are quantitative and qualitative using SPSS version 22 software using two models of analysis, namely multiple regressions, and moderated regression analysis. The results of the research are that the implementation of Bloom’s taxonomy and the understanding of taxation documents significantly influence students’ achievement in the Taxation course. Strengthened by learning motivation can moderate the implementation of Bloom’s taxonomy and understanding of taxation documents on student learning outcomes in Taxation courses with an increase in the R square value of 55.7%. This research has not used a population with bigger sample size, such as respondents from other campuses majoring in accounting and taxation. Higher education institutions can evaluate the curriculum on an ongoing basis by implementing Bloom’s taxonomy to the learning method, as well as increasing student motivation to learn from themselves and their environment. Keywords: implementation of Bloom’s taxonomy, understanding of taxation documents, learning motivation, academic achievement